CXCR6 expression predicts prognosis and immunotherapeutic benefit in muscle-invasive bladder cancer - Lu, Xiaolin; Ge, Li-Ping; Liu, Zhaopei; Zhu, Yu; Ye, Dingwei; Chang, Yuan (Frontiers in Oncology, 2024)
BackgroundIncreasing evidence suggests that the CXC chemokine receptor 6 (CXCR6) is involved in tumor progression and the regulation of tumor immunity. However, its role in muscle-invasive bladder cancer (MIBC) remains largely unexplored.MethodsData from 391 MIBC patients in the TCGA, 212 patients from GEO, 131 patients from our center, 195 patients in the IMvigor210 cohort, and single-cell RNA sequencing (scRNA-seq) data from 9 bladder cancer patients (GSE222315) were analyzed. Additionally, data from the GEPIA 2, TISCH2, TIMER2.0, and UALCAN platforms were utilized to investigate the prognostic and immunotherapeutic significance of CXCR6 in MIBC.ResultsWe observed that CXCR6 expression was significantly reduced in bladder cancer tumors and correlated with tumor stage and grade. Low CXCR6 expression was associated with poor recurrence-free survival (RFS) and overall survival (OS) in the TCGA cohort, a finding validated in both the meta-GEO dataset and our center’s cohort. Multivariate analysis confirmed that low CXCR6 expression was an independent predictor of poor OS and RFS. A nomogram incorporating CXCR6 expression and other independent prognostic factors was developed to accurately predict 3- and 5-year OS. Gene set enrichment analysis indicated that immune activation-related pathways were significantly enriched in tumors with high CXCR6 expression. CIBERSORT analysis revealed that CXCR6 expression was positively correlated with CD8+ T cells, CD4+ T cells, activated NK cells, M1 macrophages, and activated dendritic cells in TCGA, findings further validated by TIMER2.0. scRNA-seq data showed that CXCR6 was predominantly expressed in T and NK cells and facilitated T/NK-myeloid interaction via the CXCR6-CXCL16 axis. Importantly, CXCL16+ macrophages and dendritic cells recruited CXCR6+ T and NK cells, which exhibited enhanced cytotoxicity, thereby amplifying anti-tumor immunity. Clinically, in the IMvigor210 immunotherapy cohort, higher CXCR6 expression was associated with improved anti-PD-L1 therapeutic outcomes.ConclusionOur findings highlight CXCR6 as a critical biomarker for predicting prognosis and immunotherapeutic response in MIBC.